Exosomes (IntechOpen, 2024)
Exosomes - Recent Advances from Bench to Bedside is a comprehensive book exploring the field of exosomes, nanosized extracellular vesicles that regulate physiological and pathological processes. Organized into three sections, this book discusses various aspects of exosomes. The first section focuses on the use of exosomes derived from mesenchymal stem cells, including their applications in cardiovascular diseases and tissue engineering. The second section explores the role of exosomes in infectious diseases, encompassing immune reactions, pathogen transmission, and tuberculosis. The final section discusses the applications of exosomes such as drug delivery, signaling mechanisms, and even aesthetic purposes. This book provides valuable insights into the current understanding and potential applications of exosomes in diagnostics, therapeutics, and beyond.